الاقتصاد البنفسجي الرؤية الاقتصادية للثقافة في المملكة العربية السعودية: دراسة في الجغرافية السياسية - لاوند، فيان أحمد محمد (جامعة بغداد - كلية الآداب, 2022)
يعد الاقتصاد الأرجواني (البنفسج) احد أنواع الاقتصاد الذي يعد ركيزة أساسية لنمو الاقتصادي الدول كافة، ويشير اليه الاقتصاد المدمج بثقافة كما يشير لون البنفسج للأبداع ومنه جاءت التسمية، ظهر أول مره في فرنسا ٢٠١١ ومنها بدء الاهتمام بهذا النوع من الاقتصاد في الدول كافة منها المملكة العربية السعودية بعدها دولة نفطية وذات اقتصاد ناشئ تحاول الانفتاح والتوسع في مجالات التنمية كافة والتطوير الاقتصادي، فيلحظ أن القطاع الثقافي يسهم ب ٣% من أجمالي الناتج المحلي الإجمالي، فض عن امتلاكها ١٦ فرعا من الفروع الثقافية تسيطر عليها هيئة تسهل عمل تلك الفروع الثقافية. Purple Economy is one of the economic types that is considered a basic pillar of the economic development of all countries. Its name refers to the economy that is integrated with culture, and purple color is the symbol of creativity. It appeared for the first time in France from which interest started to rise in this type until it reached Saudi Arabia as it is a country of oil and a growing economy that attempts to be open and expand to all economic development and growth. It was observed that the cultural sector contributes to 3% of Gross Domestic Product as well as Saudi Arabia has 16 cultural branches directed by 11 offices that facilitate these branches' work.
Keywords: الجغرافية السياسية -- الاقتصاد البنفسجي -- القطاعات الثقافية -- السعودية